Analytical load-deflection behavior of slender load-bearing reinforced concrete walls - Alkotami, Lujain (Kansas State University, 2019)
Nearly 790 million square feet or approximately 11,000 to 12,000 buildings are constructed using tilt-up concrete panels per year since 2007 according to the Tilt-Up Concrete Association. In Tilt-Up panel design P-delta effects control slender concrete wall panel design. Therefore, understanding the nonlinear deflection behavior of these walls is the first step in refining their design, which may make them more sustainable by using less material. The American Concrete Institute (ACI) 318 Building Code Requirements for Structural Concrete provisions for slender vertical wall panels take into consideration the self-weight of the panel along with uniformly distributed lateral wind pressure in estimating the mid-height deflection. In doing so, the Branson deflection equation is used to compute central lateral displacement while adjusting for the effect of axial force. In this study, a more rigorous formulation is proposed taking into account the axial force effect on the moment curvature calculation and integration to yield more accurate load-deflection values. In this formulation, the stiffness variation along the slender wall panel allowing for un-cracked, post cracked and post yielded regions was taken into consideration. Accordingly, the full analytical load-deflection response is made available for the designers based on accurate simplifying assumptions. The developed equation is used to compare the present analytical results to some available experimental results along with the predictions of other deflection equations proposed in the literature such as the latest ACI 318, Branson and the Bischoff effective moment of inertia equations. The experimental results are full-scale panel testing data conducted by a joint venture of the Southern California Chapter of ACI and SEAOC. These results reflect representative stiffness variation of the panels beyond cracking. More specifically, the latest ACI 318 linear moment-deflection expression will be examined against the present equation that considers less simplifying assumptions. A parametric study is extended for the purpose of further proposing a simplified equation based on the rigorous approach.
Keywords: Tilt-Up; Slender walls; Deflection; Concrete